Resultados generados por haces de fotones en un maniquí simulado en Geant4 - Cañas-Varón, David Leonardo; Avilán-Betancourt, Juan David; Flórez-Pérez, José Manuel (Revista Vínculos, 2021)
This paper aims to validate the software Geant4 radiotherapy applications, generating a phantom with densities approximated to those of the CIRS 002LFC IMRT Thorax Phantom model, which is used in the characterization and calibration of X-ray beams (RX) in linear accelerators (LINAC), this is incident photon you beam RX 6 MeV generated at a distance of 100 cm from the detector set to Geant4 which is located at the isocenter of the manikin. The detector captures the energy deposited at the indicated depth as well as the dose. As a result, it is possible to build the PDD for a simulated tank and the dose in the isocenter is calculated with a number of events of the order of 106, thus demonstrating the viability of the code to generate the necessary data for more robust simulations.